Serological evidence of Erysipelothrix rhusiopathiae antibodies in wild boars (Sus scrofa) in Poland - Czyżewska-Dors Ewelina Barbara; Augustyniak Agata; Piekutowska-Nóżka Ewa; Jężak Joanna; Kowalczyk Ewelina; Jabłoński Artur (Journal of Veterinary Research)
This study aimed to evaluate the seroprevalence of Erysipelothrix rhusiopathiae among wild boars inhabiting Poland.